Positive electrode material, preparation method thereof, positive electrode sheet, battery, and electric device

CN122930873APending Publication Date: 2026-10-16HUIZHOU EVE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611161617.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

传统磷酸盐正极材料本身存在本征电化学动力学缺陷,致使其低温应用存在明显性能短板:当环境温度降至0℃以下时,电极内部锂离子扩散速率大幅放缓,电荷转移动力学过程显著受阻,进而引发电池能量密度与功率密度大幅衰减,整体低温电化学表现欠佳,亟需对正极材料进行改性优化以改善其低温适配能力

Benefits of technology

[0010]本申请的第二方面,提出一种制备第一方面所述正极材料的方法,包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930873A_ABST
    Figure CN122930873A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of batteries, and particularly relates to a positive electrode material, a preparation method thereof, a positive electrode sheet, a battery and an electric device. The positive electrode material comprises positive electrode material particles, and the positive electrode material particles comprise a phosphate inner core, an O2 phase lithium cobalt oxide functional layer and a carbon functional layer. The O2 phase lithium cobalt oxide functional layer is coated on the surface of the phosphate inner core, and the carbon functional layer is coated on the surface of the O2 phase lithium cobalt oxide functional layer away from the phosphate inner core. The O2 phase lithium cobalt oxide has the dual attributes of coating modification and active material, so that the positive electrode material has excellent rate performance and low-temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, specifically relating to cathode materials and their preparation methods, cathode sheets, batteries, and electrical devices. Background Technology

[0002] As the commercial applications of lithium-ion batteries continue to expand, extreme temperature environments such as low temperatures have become important service scenarios, and the industry's requirements for the low-temperature performance of batteries are becoming increasingly stringent. Traditional phosphate cathode materials inherently possess electrochemical kinetic defects, resulting in significant performance shortcomings in low-temperature applications: when the ambient temperature drops below 0°C, the lithium-ion diffusion rate inside the electrode slows down significantly, and the charge transfer kinetics are significantly hindered, leading to a substantial decrease in battery energy density and power density, and overall poor low-temperature electrochemical performance. Therefore, it is urgent to modify and optimize cathode materials to improve their low-temperature adaptability. Summary of the Invention

[0003] This application aims to at least partially solve one of the technical problems in the related art. To this end, this application proposes a positive electrode material with excellent rate performance and low-temperature performance, a method for preparing the same, a positive electrode sheet, a battery, and an electrical device.

[0004] In a first aspect, this application provides a cathode material comprising cathode material particles, wherein the cathode material particles comprise a phosphate core, an O2-phase lithium cobalt oxide functional layer, and a carbon functional layer, wherein the O2-phase lithium cobalt oxide functional layer covers the surface of the phosphate core, and the carbon functional layer covers the surface of the O2-phase lithium cobalt oxide functional layer away from the phosphate core.

[0005] The cathode material of this application employs a modification strategy of dual coating of a phosphate core with an O2-phase lithium cobalt oxide functional layer and a carbon functional layer, synergistically optimizing the electrochemical performance and interfacial stability of the phosphate core. The O2-phase lithium cobalt oxide possesses a low lithium-ion migration barrier, significantly reducing interfacial lithium insertion / extraction resistance, optimizing interfacial ion transport kinetics at low temperatures, and effectively alleviating interfacial polarization problems under low-temperature conditions. Simultaneously, as an active lithium source, it can achieve in-situ lithium replenishment during the modification of the phosphate material surface, compensating for active lithium loss during cycling and simultaneously improving initial coulombic efficiency and cycle life. Furthermore, the O2-phase lithium cobalt oxide coating physically isolates the phosphate material from the electrolyte, suppressing interfacial side reactions and iron dissolution, while the carbon layer further enhances electronic conductivity and structural toughness. This dual coating synergistically stabilizes the electrode-electrolyte interface and crystal structure. Based on this, the O2 phase lithium cobalt oxide and the carbon layer synergistically construct a high-speed electron-ion hybrid conductive network, which makes up for the deficiency of intrinsic electronic conductivity of phosphate materials. This significantly reduces the polarization of the cathode material under fast charging conditions and greatly improves the rate discharge performance. At the same time, it effectively suppresses the capacity decay and polarization increase problems at low temperatures.

[0006] According to embodiments of this application, the phosphate core comprises the compound shown in Formula 1: LiFe a M b PO4 Formula 1 Wherein, 1≥a>0.5, b≥0, and a+b=1, and M includes at least one of Ni, Co, Mn, Ti, Al, F, B, Si, V, W, Y, Mg, Na, Nb, N, and Ca.

[0007] According to embodiments of this application, the O2 phase lithium cobalt oxide functional layer comprises the compound shown in Formula 2: Li x Co m X n O2 type 2 Wherein, 0.5≤x<1, 1≥m>0.5, n≥0, and a+b=1, and X includes at least one of Ni, Mn, Ti, Al, F, B, Si, V, W, Y, Mg, Na, Nb, N, and Ca.

[0008] According to embodiments of this application, the above-mentioned cathode material satisfies at least one of the following conditions: The carbon functional layer accounts for 0.1 wt% to 10 wt% of the total mass of the cathode material; The O2 phase lithium cobalt oxide functional layer accounts for 0.1wt% to 5wt% of the total mass of the cathode material.

[0009] According to an embodiment of this application, the O2 phase lithium cobalt oxide functional layer includes a porous structure, and at least a portion of the carbon functional layer fills the porous structure of the O2 phase lithium cobalt oxide functional layer.

[0010] A second aspect of this application provides a method for preparing the cathode material described in the first aspect, comprising: An O2 phase lithium cobalt oxide functional layer is formed on the phosphate surface to obtain the first product; A carbon functional layer is formed on the surface of the first product to obtain a cathode material.

[0011] This method is simple to operate, low in cost, environmentally friendly, and easy to scale up for production.

[0012] According to embodiments of this application, an O2-phase lithium cobalt oxide functional layer is formed on the surface of a phosphate to obtain a first product, comprising: Provide P2 phase sodium cobaltate; The P2 phase sodium cobaltate and phosphate are mixed and coated, and then subjected to a first sintering, so that the P2 phase sodium cobaltate is coated on the surface of the phosphate to obtain an intermediate product. The intermediate product and lithium source are mixed and subjected to an ion exchange reaction to form an O2 phase lithium cobalt oxide functional layer on the phosphate surface, thus obtaining the first product. The first product and a carbon source are mixed and carbonized to form a carbon functional layer on the surface of the first product, thus obtaining a cathode material.

[0013] According to embodiments of this application, the above method satisfies at least one of the following conditions: The mass ratio of the P2 phase sodium cobaltate to the phosphate is 0.1~5; The molar ratio of sodium in the P2 phase sodium cobaltate to lithium in the lithium source is 1:2~20; The mass of the carbon source is 8wt% to 20wt% of the mass of the phosphate.

[0014] According to embodiments of this application, the above method satisfies at least one of the following conditions: The lithium source includes at least one of LiCl, LiNO3, and LiOH; The carbon source includes at least one of ascorbic acid, α-naphthol, o-naphthol, D-sorbitol, citric acid, oxalic acid, and chitosan.

[0015] According to embodiments of this application, the above method satisfies at least one of the following conditions: The temperature of the first sintering is 200 ℃~900 ℃; The first sintering time is 3 h to 22 h; The heating rate for the first sintering is 0.5 ℃ / min to 8 ℃ / min; The temperature of the ion exchange reaction is 100 ℃ to 400 ℃; The ion exchange reaction takes 0.5 h to 7 h; The carbonization treatment temperature is 180 ℃-400 ℃; The carbonization process takes 3-8 hours. The atmosphere for the carbonization process includes an inert gas.

[0016] A third aspect of this application provides a positive electrode sheet comprising the positive electrode material described in the first aspect and the positive electrode material prepared by the method described in the second aspect. This positive electrode sheet incorporates all the features and advantages of the positive electrode material described in the first aspect and the positive electrode material prepared by the method described in the second aspect, which will not be elaborated upon here.

[0017] A fourth aspect of this application provides a battery comprising the positive electrode material described in the first aspect, the positive electrode material prepared by the method described in the second aspect, or the positive electrode sheet described in the third aspect. This battery exhibits excellent rate performance and low-temperature performance.

[0018] A fifth aspect of this application provides an electrical device comprising the positive electrode material described in the first aspect, the positive electrode material prepared by the method described in the second aspect, the positive electrode sheet described in the third aspect, or the battery described in the fourth aspect. This electrical device includes all the features and advantages of the positive electrode material described in the first aspect, the positive electrode material prepared by the method described in the second aspect, the positive electrode sheet described in the third aspect, or the battery described in the fourth aspect, which will not be elaborated upon here. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the structure of a cathode material according to an embodiment of this application.

[0020] Figure 2 This is a SEM image of the cathode material of Embodiment 1 of this application.

[0021] Figure 3 This is a SEM image of the cathode material of Comparative Example 1 of this application.

[0022] Figure 4 This is a SEM image of the cathode material of Comparative Example 2 of this application. Detailed Implementation

[0023] The embodiments of this application are described in detail below, with examples of these embodiments illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain this application, and should not be construed as limiting this application.

[0024] As the commercial applications of lithium-ion batteries continue to expand, extreme temperature environments such as low temperatures have become important service scenarios, and the industry's requirements for the low-temperature performance of batteries are becoming increasingly stringent. However, phosphate materials themselves have inherent electrochemical kinetic defects, which directly lead to insurmountable performance bottlenecks in low-temperature environments: when the ambient temperature drops below 0°C, the lithium-ion diffusion rate inside the electrode slows down significantly, the charge transfer kinetics are significantly hindered, and this leads to a significant decrease in battery energy density and power density. This technical challenge has become the core obstacle restricting the large-scale application of low-temperature phosphate batteries. Current industry research on optimizing the low-temperature performance of lithium-ion batteries largely focuses on single technical dimensions such as cathode material structure modification and electrolyte formulation optimization, generally neglecting the core regulatory role of the electrode-electrolyte interface under low-temperature conditions. Surface coating modification of cathode materials is an efficient and feasible strategy for regulating the properties of the cathode-electrolyte interface and improving the low-temperature performance of lithium-ion batteries. Based on the core functions of the coating layer, surface coating technologies for improving the low-temperature performance of lithium-ion batteries can be mainly divided into three categories: first, improving the electronic conductivity of the electrode material itself and optimizing charge transport efficiency; second, isolating the electrode material from the electrolyte through physical barriers to effectively suppress interfacial side reactions; and third, optimizing the solid electrolyte interphase (SEI) film structure to directly reduce interfacial charge transfer resistance. Based on this technical logic, targeted surface coating modification of phosphate materials is a feasible technical path to achieve a significant improvement in their low-temperature performance.

[0025] Phosphate materials have an olivine-type framework structure (such as lithium iron phosphate and lithium manganese iron phosphate), where lithium ions can only diffuse along one-dimensional directional channels. They inherently have a low ion diffusion coefficient and extremely poor electronic conductivity. At low temperatures (below 0°C), the lithium-ion migration barrier increases significantly, and the diffusion rate and charge transfer kinetics slow down exponentially, which is the core reason for their poor low-temperature performance. In contrast, O2-phase lithium cobalt oxide has a layered stacked structure, allowing lithium ions to migrate rapidly along two-dimensional interlayer channels. Its intrinsic ion diffusion coefficient is much higher than that of conventional phosphate materials. At low temperatures, ion transport is less hindered, and the charge transfer barrier is lower. Even under low-temperature conditions, it maintains more efficient lithium-ion insertion / extraction kinetics, and the electrode polarization is much lower than that of phosphate materials. Furthermore, O2-phase lithium cobalt oxide belongs to the P63mc space group, unlike the ABCABC oxygen stacking of O3-phase lithium cobalt oxide and ternary cathode materials (such as NCM, R-3m space group). This stacking method gives it higher Li-energy permeability. + The diffusion coefficient and better mechanical stability make the lithium-ion diffusion rate superior to that of O3 phase lithium cobalt oxide and ternary cathode materials (such as nickel-cobalt-manganese NCM ternary materials). Therefore, when O2 phase lithium cobalt oxide is used as a coating layer, its rate performance is significantly better than that of ternary cathode materials and O3 phase lithium cobalt oxide.

[0026] This application first constructs an O2-phase lithium cobalt oxide phase coating layer on the surface of phosphate, and then further modifies it with carbon coating on the outer layer. By using a two-layer composite modification strategy to synergistically optimize the interfacial conductive network, the electronic conductivity of the phosphate material is effectively improved, thereby enhancing its rate electrochemical performance and low-temperature cycling adaptability.

[0027] Based on the above, the first aspect of this application proposes a cathode material. (Refer to...) Figure 1The cathode material includes cathode material particles, wherein the cathode material particles include a phosphate core, an O2 phase lithium cobalt oxide functional layer and a carbon functional layer, the O2 phase lithium cobalt oxide functional layer covers the surface of the phosphate core, and the carbon functional layer covers the surface of the O2 phase lithium cobalt oxide functional layer away from the phosphate core.

[0028] The cathode material of this application employs a dual coating strategy of O2-phase lithium cobalt oxide and a carbon layer to synergistically optimize the electrochemical performance and interfacial stability of the phosphate matrix. O2-phase lithium cobalt oxide possesses a low lithium-ion migration barrier, significantly reducing interfacial lithium insertion / extraction resistance, optimizing interfacial ion transport kinetics at low temperatures, and effectively alleviating interfacial polarization problems under low-temperature conditions. Simultaneously, as an active lithium source, it can achieve in-situ lithium replenishment during the modification of the phosphate core surface, compensating for active lithium loss during cycling and simultaneously improving initial coulombic efficiency and cycle life. Furthermore, the O2-phase lithium cobalt oxide coating physically isolates the phosphate core from the electrolyte, suppressing interfacial side reactions and iron dissolution, while the carbon layer further enhances electronic conductivity and structural toughness. This dual coating synergistically stabilizes the electrode-electrolyte interface and crystal structure. Based on this, the O2 phase lithium cobalt oxide and the carbon layer synergistically construct a high-speed electron-ion hybrid conductive network, which makes up for the deficiency of intrinsic electronic conductivity of the phosphate core. This significantly reduces the polarization of the cathode material under fast charging conditions and greatly improves the rate discharge performance. At the same time, it effectively suppresses the capacity decay and polarization increase problems at low temperatures.

[0029] According to embodiments of this application, the phosphate core comprises the compound shown in Formula 1: LiFe a M b PO4 Formula 1 Wherein, 1≥a>0.5, b≥0, and a+b=1, and M includes at least one of Ni, Co, Mn, Ti, Al, F, B, Si, V, W, Y, Mg, Na, Nb, N, and Ca.

[0030] According to embodiments of this application, the O2 phase lithium cobalt oxide functional layer comprises the compound shown in Formula 2: Li x Co m X n O2 type 2 Wherein, 0.5≤x<1, 1≥m>0.5, n≥0, and a+b=1, and X includes at least one of Ni, Mn, Ti, Al, F, B, Si, V, W, Y, Mg, Na, Nb, N, and Ca.

[0031] According to embodiments of this application, the carbon functional layer accounts for 0.1 wt% to 10 wt% of the total mass of the cathode material, specifically 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, or any range between two of these. Within the above range, the carbon functional layer can form a continuous conductive network on the surface of the O2 phase lithium cobalt oxide functional layer, effectively improving electronic conductivity and buffering volumetric strain. If the above proportion is too low, it may lead to discontinuous coating of the carbon layer; if the above proportion is too high, the carbon functional layer will be thicker, which may hinder lithium-ion transport and reduce rate performance.

[0032] According to embodiments of this application, the O2-phase lithium cobalt oxide functional layer accounts for 0.1wt% to 5wt% of the total mass of the cathode material, specifically 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, or any two of these ranges. Within the above range, the O2-phase lithium cobalt oxide can effectively reduce interfacial lithium insertion / extraction resistance, achieve in-situ lithium replenishment, and suppress interfacial side reactions. If the above proportion is too low, the O2-phase lithium cobalt oxide functional layer may not be fully coated; if the above proportion is too high, the thicker the O2-phase lithium cobalt oxide functional layer, the greater the ion diffusion path may be, thereby reducing rate performance and cycle performance.

[0033] According to an embodiment of this application, the O2-phase lithium cobalt oxide functional layer includes a porous structure, with at least a portion of the carbon functional layer filling the porous structure of the O2-phase lithium cobalt oxide functional layer. This improves the bonding force between the O2-phase lithium cobalt oxide functional layer and the carbon functional layer, thereby reducing the breakage of ion transport channels and the continuous increase in interface impedance during cycling, ensuring the stable continuity of the conductive network.

[0034] A second aspect of this application provides a method for preparing the cathode material described in the first aspect, comprising: An O2-phase lithium cobalt oxide functional layer is formed on the phosphate surface to obtain a first product; a carbon functional layer is formed on the surface of the first product to obtain a cathode material.

[0035] The above method is simple to operate, low in cost, and easy to scale up. Furthermore, there are no specific restrictions on the method for forming the O2 phase lithium cobalt oxide functional layer; it can be flexibly selected according to specific needs.

[0036] According to an embodiment of this application, as a specific example, an O2 phase lithium cobalt oxide functional layer is formed on the surface of a phosphate to obtain a first product, comprising: S10: Provides sodium cobaltate in the P2 phase.

[0037] According to embodiments of this application, the preparation process of P2 phase sodium cobaltate is carried out using conventional methods. As a specific example, a sodium source, a cobalt source, and optionally an X source are mixed according to the stoichiometric ratio of the target chemical formula, wherein the excess sodium ratio is 0.01%-0.05%. The mixture is heated to 800℃-1000℃ in air and sintered for 8-14 hours. The resulting material is then subjected to primary crushing using a jaw crusher, secondary crushing using an air jet mill, and tertiary crushing using a high-energy ball mill to obtain X-element-doped P2 phase sodium cobaltate or directly obtain undoped P2 phase sodium cobaltate. The excess sodium ratio is defined as (actual amount of sodium added - theoretical stoichiometric sodium amount) / theoretical stoichiometric sodium amount × 100%. For example, an excess sodium ratio of 0.05% means that the actual amount of sodium added is 0.05% more than the theoretical stoichiometric sodium amount.

[0038] According to embodiments of this application, the sodium source includes, but is not limited to, Na2CO3, NaOH, NaCl, NaNO3, sodium oxalate, etc.

[0039] According to embodiments of this application, the cobalt source includes, but is not limited to, Co3O4, CoOOH, etc.

[0040] According to embodiments of this application, the X source includes at least one selected from the following: oxide of X, oxalate of X, nitrate of X, and chloride of X. Exemplary examples of X sources include titanium dioxide, magnesium oxide, yttrium oxide, sodium hydroxide, etc.

[0041] S20: The P2 phase sodium cobaltate and phosphate are mixed and coated, and a first sintering is performed to coat the surface of the phosphate with the P2 phase sodium cobaltate, thereby obtaining an intermediate product.

[0042] In this step, the obtained P2 phase sodium cobaltate and phosphate are mixed, so that the P2 phase sodium cobaltate coats the surface of the phosphate. During sintering, elements diffuse at the interface, forming a well-bonded interface and constructing a continuous electron conduction channel. The mixing method and specific operating parameters are not specifically limited, as long as the two are mixed uniformly. Specific methods can be flexibly selected according to actual conditions.

[0043] According to the embodiments of this application, phosphates can be directly purchased as pure phosphate materials or prepared by oneself. The specific operation process for preparing phosphates by oneself can refer to conventional techniques. As a specific example, taking LiFePO4 as an example, the preparation steps include: weighing the raw materials, such as iron source, lithium salt, phosphorus source, and optional dopant element according to the molar ratio of the target chemical formula, organic reducing agent (such as ascorbic acid), and surfactant (such as hexadecyl ammonium bromide (CTAB)). First, CTAB is dissolved in a mixed solvent of H2O and ethylene glycol (volume ratio of 3:5). 1 / 4 of the above mixed solution is used to dissolve the lithium salt. After stirring for a period of time, the weighed phosphorus source is added, and stirring is continued until a uniform white solution is formed. The iron source or iron source and M source are dissolved in the remaining 3 / 4 of the mixed solution to obtain an iron source solution. The above white solution is slowly added dropwise to the iron source solution, and an appropriate amount of ascorbic acid solution is added dropwise to prevent the oxidation of ferrous ions. The mixed solution is stirred for 2-2.5 hours. Subsequently, the mixed solution is placed in an oil bath at 150-190℃ for 7 hours. After the reaction is complete, the obtained precipitate is washed with deionized water and ethanol, the precipitate is collected, and the moisture is dried to obtain the LiFePO4 precursor. The solid powder is then sintered under an inert atmosphere (such as nitrogen) at a heating rate of 0.5℃ / min–8℃ / min to 300℃–1500℃, and held at this temperature for 3–22 hours to obtain LiFePO4 or LiFe a M b PO 4。

[0044] According to embodiments of this application, the iron source includes at least one of oxides, oxalates, sulfates, nitrates, chlorides, and phosphates. For example, the iron source may be FeSO4·7H2O.

[0045] According to embodiments of this application, the lithium salt includes at least one selected from lithium nitrate, lithium chloride, lithium carbonate, lithium acetate, and lithium hydroxide. For example, the lithium salt may be LiOH·H₂O.

[0046] According to embodiments of this application, the phosphorus source includes, but is not limited to, H3PO4, FePO4, etc.

[0047] According to embodiments of this application, the source M includes at least one selected from the following: oxide of M, oxalate of M, sulfate of M, nitrate of M, and chloride of M. For example, the source M may be TiO2.

[0048] According to embodiments of this application, the mass ratio of the P2 phase sodium cobaltate to the phosphate is 0.1 to 5, specifically within the ranges of 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, or any two of these ranges. Within these ranges, a uniform, continuous, and appropriately thick P2 phase sodium cobaltate layer can be formed on the phosphate surface, thereby contributing to obtaining a cathode material with good overall performance.

[0049] According to an embodiment of this application, the first sintering temperature is 200℃~900℃, specifically 200℃, 300℃, 400℃, 500℃, 600℃, 700℃, 800℃, 900℃, or any range between two of these. Within the above sintering temperature range, the interfacial bonding between the phosphate and the P2 phase sodium cobaltate is strong, the coating is uniform and complete, and the P2 phase structure can be kept intact.

[0050] According to an embodiment of this application, the first sintering time is 3h to 22h, specifically 3h, 5h, 10h, 15h, 18h, 20h, 22h, or any two of these ranges. Within the above sintering time range, a continuous and uniform P2 phase sodium cobalt oxide coating layer can be sufficiently formed, while maintaining the integrity of the P2 phase structure, without wasting time.

[0051] According to embodiments of this application, the heating rate of the first sintering is 0.5℃ / min to 8℃ / min, specifically within the ranges of 0.5℃ / min, 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, or any two of these ranges. Within these ranges, heating is uniform, sintering stress can be released evenly, and this helps to form a well-bonded interface.

[0052] S30: The intermediate product and lithium source are mixed and subjected to an ion exchange reaction to form an O2 phase lithium cobalt oxide functional layer on the phosphate surface, thus obtaining the first product.

[0053] The first product and a lithium source were mixed and subjected to an ion exchange reaction, in which sodium ions in the P2 phase were replaced by lithium ions. Due to the Li... + Its radius is 0.76 Å, much smaller than that of Na. + The radius (1.02 Å) cannot stably occupy the triangular prism voids of the P2 phase; after exchange, it must be converted into octahedral coordination (O site) to trigger structural reconstruction and obtain the O2 phase lithium cobalt oxide.

[0054] According to embodiments of this application, the molar ratio of sodium in the P2 phase sodium cobaltate to lithium in the lithium source is 1:2 to 20. Specifically, the molar ratio of sodium in the P2 phase sodium cobaltate to lithium in the lithium source can be 1:2, 1:5, 1:8, 1:11, 1:14, 1:17, 1:20, or any combination thereof. Within the above range, sodium ions can be fully replaced by lithium ions, and the P2 phase sodium cobaltate can be completely converted into O2 phase lithium cobaltate.

[0055] According to embodiments of this application, the lithium source includes at least one of LiCl, LiNO3, and LiOH. These lithium sources are widely available and readily accessible. In some embodiments, the lithium source participates in the reaction in a molten state during the ion exchange reaction, wherein LiCl and LiNO3 can be combined to form a eutectic salt system, which can effectively reduce the reaction temperature and improve the ion exchange reaction efficiency. The ion exchange reaction can also be carried out in solution.

[0056] According to embodiments of this application, the temperature of the ion exchange reaction is 100℃~400℃, specifically, the ion exchange temperature is 100℃, 200℃, 300℃, 400℃, or any two of these temperatures. Within this range, sodium ions can be fully replaced by lithium ions, thereby completely converting P2 phase sodium cobalt oxide into pure O2 phase lithium cobalt oxide.

[0057] According to embodiments of this application, the ion exchange reaction time is 0.5h to 7h, specifically 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, or any range between two of these. Within this range, sodium ions can be fully replaced by lithium ions, thereby completely converting P2 phase sodium cobalt oxide into pure O2 phase lithium cobalt oxide.

[0058] According to embodiments of this application, after the ion exchange reaction is completed, the product is washed with solvents such as H2O, ethanol, or ethylene glycol. This removes impurity ions adhering to the surface of the first product.

[0059] S40: The first product and the carbon source are mixed and carbonized to form a carbon functional layer on the surface of the first product, thereby obtaining a cathode material.

[0060] In this step, there are no specific restrictions on the mixing method, as long as the carbon source adheres to the surface of the first product. During the carbonization process, the carbon source undergoes structural rearrangement to form a conductive carbon framework; at the same time, it enhances the interfacial bonding with the O2 phase lithium cobalt oxide through chemical bonding or physical intercalation, constructing electron and ion transport channels.

[0061] According to embodiments of this application, the mass of the carbon source is 8 wt% to 20 wt% of the theoretical mass of the phosphate, specifically within the range of 8 wt%, 10 wt%, 12 wt%, 14 wt%, 16 wt%, 18 wt%, 20 wt%, or any two of these ranges. Within this range, a uniform, continuous carbon functional layer of suitable thickness can be formed.

[0062] According to embodiments of this application, the methods for forming a carbon functional layer on the surface of the first product include, but are not limited to, solid-state sintering, liquid-phase wet coating, and vapor deposition. The specific method can be flexibly selected based on actual needs and the type of carbon source.

[0063] According to embodiments of this application, the carbon source includes at least one selected from ascorbic acid, α-naphthol, o-naphthol, D-sorbitol, citric acid, oxalic acid, and chitosan. Therefore, the aforementioned carbon source is widely available and inexpensive.

[0064] According to an embodiment of this application, forming a carbon functional layer on the surface of the first product includes: mixing the first product and a carbon source and performing a carbonization treatment, so that at least a portion of the carbon functional layer fills the porous structure of the O2 phase lithium cobalt oxide functional layer. The carbonization treatment includes solid-phase mixing and coating, vapor deposition, etc.

[0065] For example, when using ascorbic acid, a carbon functional layer can be formed on the surface of O2-phase lithium cobalt oxide using pulsed high-pressure vapor deposition. The thickness of the carbon functional layer can be flexibly adjusted by precisely controlling the reaction temperature and pulse pressure parameters. The point-to-point contact gaps and nanoporous structures on the surface of the O2-phase lithium cobalt oxide coating layer serve as adsorption channels (the O2-phase lithium cobalt oxide coating layer has nanoscale micropores; the coating layer is deposited on the core surface in particle form, with particles arranged in point contact, forming gaps between contact areas). Under high-temperature conditions, ascorbic acid is fully evaporated and forms active polymeric gaseous clusters. Then, through multiple cycles of inert gas pulse pressure adsorption, the gaseous carbon clusters are uniformly filled and enriched within the micropores and interfacial pores of the O2-phase lithium cobalt oxide coating layer.

[0066] According to embodiments of this application, the carbonization temperature is 180℃-400℃, specifically 180℃, 200℃, 300℃, 400℃, etc. Within this range, the carbon source entering the pores of the O2 phase lithium cobalt oxide undergoes pyrolysis and solidification, achieving pore sealing and dense reinforcement, ultimately obtaining a cathode material with complete pore sealing of the O2 phase lithium cobalt oxide functional layer and uniform carbon functional layer coating. This process facilitates the complete pyrolysis of the carbon source into a highly conductive carbon framework, constructing efficient electron and ion transport channels.

[0067] According to embodiments of this application, the carbonization treatment time is 3-8 hours, specifically 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc. Within the above range, the carbon source entering the pores of the O2 phase lithium cobalt oxide is fully pyrolyzed and solidified, achieving pore sealing and structural densification and reinforcement. This process helps the carbon source to be fully pyrolyzed and transformed into a highly conductive carbon framework, constructing efficient electron and ion transport channels.

[0068] According to embodiments of this application, the carbonization process is carried out in an inert gas atmosphere, such as a nitrogen atmosphere or an argon atmosphere. An inert gas atmosphere helps prevent carbon from being oxidized at high temperatures.

[0069] A third aspect of this application provides a positive electrode sheet comprising the positive electrode material described in the first aspect and the positive electrode material prepared by the method described in the second aspect. This positive electrode sheet incorporates all the features and advantages of the positive electrode material described in the first aspect and the positive electrode material prepared by the method described in the second aspect, which will not be elaborated upon here.

[0070] A fourth aspect of this application provides a battery comprising the positive electrode material described in the first aspect, the positive electrode material prepared by the method described in the second aspect, or the positive electrode sheet described in the third aspect. This battery exhibits excellent rate performance and low-temperature performance.

[0071] It is understood that there are no particular restrictions on the specific types and structures of the batteries mentioned above, as long as they require positive electrode materials. For example, according to performance classification, batteries can include, but are not limited to, primary batteries, secondary batteries, etc. According to shape classification, batteries can include, but are not limited to, prismatic batteries, cylindrical batteries, etc.; according to outer packaging classification, batteries can include, but are not limited to, pouch batteries, hard-shell batteries, etc.

[0072] Typically, a battery may include the positive electrode, negative electrode, electrolyte, and separator mentioned above.

[0073] According to the embodiments of this application, in the battery described above, the electrolyte can be a liquid electrolyte (i.e., an electrolyte solution) or a solid electrolyte.

[0074] According to embodiments of this application, the electrolyte is a liquid electrolyte. In this case, the positive electrode, negative electrode, and separator can be fabricated into a battery cell using a winding or stacking process. The battery cell and electrolyte can be housed in an outer packaging. During battery charging and discharging, active ions repeatedly insert and extract between the positive and negative electrode plates. The electrolyte acts as a conductor of ions between the positive and negative electrode plates. The separator is positioned between the positive and negative electrode plates, primarily serving to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through.

[0075] According to an embodiment of this application, the electrolyte is a solid electrolyte. In this case, the positive electrode, negative electrode, electrolyte, and battery separator can be manufactured into a battery cell through a winding or stacking process, and the battery cell can be housed in an outer package. The positive and negative electrode sheets are alternately stacked, and the electrolyte and battery separator are disposed between adjacent positive and negative electrode sheets.

[0076] According to an embodiment of this application, the negative electrode sheet comprises a lithium metal sheet.

[0077] According to an embodiment of this application, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located at least on one side of the negative electrode sheet, the negative electrode active material layer including a negative electrode active material.

[0078] According to embodiments of this application, the negative current collector includes copper foil or aluminum foil.

[0079] According to embodiments of this application, the negative electrode active material layer may include a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder.

[0080] According to embodiments of this application, the negative electrode active material may include carbon-based materials (such as hard carbon, soft carbon, etc.), metals and their compounds, organic compound materials, etc.

[0081] According to embodiments of this application, the negative electrode binder in the negative electrode active material layer includes at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0082] According to embodiments of this application, the negative electrode conductive agent in the negative electrode active material layer includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0083] According to embodiments of this application, the diaphragm includes polyethylene diaphragm, polypropylene diaphragm, polyethylene / polypropylene composite diaphragm, etc.

[0084] A fifth aspect of this application provides an electrical device, characterized in that it comprises the positive electrode material described in the first aspect, the positive electrode material prepared by the method described in the second aspect, the positive electrode sheet described in the third aspect, or the battery described in the fourth aspect. This electrical device incorporates all the features and advantages of the positive electrode material described in the first aspect, the positive electrode material prepared by the method described in the second aspect, the positive electrode sheet described in the third aspect, or the battery described in the fourth aspect, which will not be elaborated upon here.

[0085] It is understood that there are no particular restrictions on the specific type of electrical device, and it can be any device that uses a battery as a power source or energy storage unit. As examples, electrical devices include, but are not limited to, electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), mobile terminals (such as mobile phones, laptops, game consoles, wearable devices, etc.), drones, aerospace equipment, satellites, ships, energy storage systems, and so on.

[0086] It is understandable that, in addition to the battery mentioned above, the electrical device also includes necessary structures and components, all of which can be made with reference to conventional technologies. For example, an electric vehicle may include a body, chassis, tires, navigation system, radar system, steering system, braking system, lubrication system, cooling system, driving system, etc., which will not be described in detail here.

[0087] The embodiments of this application are described in detail below.

[0088] Example 1 (1) Preparation of phosphate kernel Ferrous sulfate heptahydrate (FeSO4·7H2O) was used as the iron source, lithium hydroxide heptahydrate (LiOH·H2O) as the lithium salt, phosphoric acid (H3PO4) as the phosphorus source, ascorbic acid as the organic reducing agent, and hexadecyltrimethylammonium bromide (CTAB) as the surfactant. The metal raw materials were fed in a ratio of Fe:Li:P of 1:1:1.

[0089] First, at 25°C, 100 mL of a mixed solvent was prepared by mixing deionized water and ethylene glycol at a volume ratio of 3:5. CTAB (0.35% of the total mass of the mixed solvent) was added to the mixed solvent and stirred thoroughly until completely dissolved, yielding a homogeneous precursor solution. Then, 1 / 4 volume of the above mixed precursor solution was taken, and LiOH·7H2O was added, with stirring continued for 20 min. Next, H3PO4 was added according to the set molar ratio, and stirring was continued at a constant temperature for 1 h until a clear, homogeneous white mixed solution was formed. FeSO4·7H2O was completely dissolved in the remaining 3 / 4 volume of the precursor solution to obtain a ferrous sulfate mixed solution. The above white mixed solution was slowly added dropwise to the ferrous sulfate mixed solution, simultaneously adding ascorbic acid at a mass of 0.5 wt% relative to the target LFP, while continuously stirring the mixture for 2 h to ensure thorough mixing and reaction of all raw materials.

[0090] After stirring, the mixed reaction system was placed in an oil bath at 180℃ and kept at that temperature for 7 hours. After the reaction, the precipitated product was collected and washed repeatedly with deionized water and ethanol in sequence; then dried to obtain LiFePO4 precursor powder.

[0091] Finally, the dried precursor powder was placed in an argon atmosphere for high-temperature sintering. The temperature was increased to 800°C at a rate of 5°C / min, and the temperature was held constant for 6 hours. After sintering, the powder was cooled to room temperature in the furnace to obtain the LiFePO4 core material (LFP).

[0092] (2) Preparation of P2 phase sodium cobaltate Na₂CO₃ was selected as the sodium source, Co₃O₄ as the cobalt source, and TiO₂ as the titanium source. The corresponding metal salts were added according to the stoichiometric ratio of the target compound, with a sodium excess of 0.05%. The metal salts were mixed and sintered in air at 950°C for 12 hours. The resulting material was then subjected to primary pulverization using a jaw crusher, secondary pulverization using an air jet mill, and tertiary pulverization using a high-energy ball mill to obtain Ti-doped P₂ phase sodium cobaltate (Na₂CO₃). 0.67 Co 0.9 Ti 0.1 O2).

[0093] (3) Preparation of O2 phase lithium cobalt oxide functional layer The aforementioned LiFePO4 core material and Ti-doped P2-phase sodium cobaltate were mixed, and the mixture was heated to 650°C in air at a heating rate of 5°C / min and held for 6 hours to obtain Ti-doped P2-phase sodium cobaltate-coated lithium iron phosphate. A LiNO3 and LiCl complex system with a mass ratio of 88:12 was selected as the lithium source for the low eutectic compound system, with a Li:Na exchange molar ratio of 10:1. The Ti-doped P2-phase sodium cobaltate-coated lithium iron phosphate was mixed uniformly with the lithium source, and an ion exchange reaction was carried out in air at 350°C for 3 hours. After repeated washing with deionized water and ethanol, O2-phase Ti-doped lithium cobaltate (LiFePO4) was obtained. 0.67 Co 0.9 Ti 0.1 Lithium iron phosphate coated with O2.

[0094] (4) Preparation of cathode materials High-purity nitrogen at 0.5 MPa pressure was used as the carrier gas, and ascorbic acid was used as the carbon source. The ascorbic acid was fully evaporated at 160 °C for 60 min to form active polymer gaseous clusters. Inert gas cyclic permeation adsorption was performed: the pressure was 1 MPa, and the pulse pressure was 0.2 MPa, that is, 10 pulses at 1.2 MPa, so that the gaseous carbon clusters were uniformly filled and enriched in the micropores and interfacial voids of the coating layer. After the adsorption was saturated, the powder was further heated in an inert atmosphere (Ar) and subjected to high-temperature carbonization treatment at 320 °C for 4 h to form a carbon functional layer, and finally the cathode material was obtained.

[0095] (5) Preparation of button cells The above-mentioned positive electrode material, conductive carbon black SP, and binder polyvinylidene fluoride PVDF were mixed thoroughly at a mass ratio of 92%:5%:3%. A uniform and stable positive electrode slurry was prepared by dispersing and stirring with N-methylpyrrolidone (NMP) as the solvent system. The obtained positive electrode slurry was uniformly coated onto the surface of an aluminum foil current collector, and then dried at 100℃ for 1.5 h. Rolling was performed with the roller gap adjusted to 0.45 mm to control the electrode compaction to 2.3 g / cm³. 3 The positive electrode plate.

[0096] The electrolyte used is 1.0 M LiPF6, ethylene carbonate: dimethyl carbonate (EC:DMC) = 1:1 (volume ratio).

[0097] Diaphragm: The diaphragm is made of polyethylene (PE) and is composed of a 9μm layer and a 3μm layer.

[0098] The CR2430 coin cell was assembled in the following order: negative electrode shell → nickel foam → lithium sheet → electrolyte addition → separator → electrolyte replenishment → positive electrode sheet → gasket → positive electrode shell. After assembly, the battery was left to stand at room temperature for 3 hours for activation testing.

[0099] The aforementioned CR2430 coin cell can be used to evaluate the rate performance (10C / 0.2C, 5C / 0.2C, 2C / 0.2C) and charge / discharge plateau potential difference of the cathode material at room temperature.

[0100] (6) Preparation of full cells The raw materials were weighed according to the following mass ratios: lithium iron phosphate (LFP) 95.7%, carbon nanotubes (CNT) 0.5%, conductive carbon black (SP) 2.0%, polyvinylidene fluoride (PVDF) 1.6%, and dispersant 0.2%. All the weighed solid powders were added to a vacuum mixer for premixing to ensure uniform dispersion of each powder component. Then, N-methylpyrrolidone (NMP) was added as a dispersion solvent, and the mixture was continuously stirred until the slurry was free of obvious particles, homogeneous, and stable, thus obtaining the positive electrode slurry. This slurry was then uniformly coated onto the surface of an aluminum foil current collector using a coating device. After coating, it was transferred to a vacuum drying oven and dried at a constant temperature of 100℃ for 1.5 hours to remove the solvent from the positive electrode slurry. The dried electrode sheet was then rolled to ensure a suitable compaction density of 2.38 g / cm³. 3 The raw materials are then cut to produce standard positive electrode sheets that meet specifications. The raw materials are weighed according to the following mass ratios: 96.4% graphite, 0.9% conductive carbon black (SP), 1.2% sodium carboxymethyl cellulose (CMC), and 1.5% styrene-butadiene rubber (SBR). Using deionized water as the dispersion solvent, each component is added sequentially in the order of "binder-conductive agent-negative electrode active material," gradually dispersing and mixing while continuously stirring until a homogeneous, agglomerated negative electrode slurry is prepared. The negative electrode slurry is uniformly coated onto the surface of a copper foil current collector, dried to remove moisture, and then rolled to adjust the compaction density to 1.55 g / cm³. 3 After cutting and trimming to size, standard negative electrode sheets are obtained. Electrolyte: 1.0 mol / L LiPF6, ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate (EC:DMC:EMC) = 3:4:3 (volume ratio), additives are 2% vinylene carbonate (VC) + 4% fluoroethylene carbonate (FEC) (all percentages are mass fractions, calculated based on the total mass of the electrolyte).

[0101] Diaphragm: The diaphragm is made of polyethylene (PE) and is composed of a 9μm layer and a 3μm layer.

[0102] After the positive and negative electrode sheets are prepared, the subsequent processes such as cell winding, shell packaging, electrolyte injection and formation are completed in sequence according to the preset process flow, and finally the full cell to be tested is obtained.

[0103] The above full cells were used to test the rate performance of the cathode material at -20°C (0.33C / 0.2C, 1C / 0.2C, 2C / 0.2C, 5C / 0.2C).

[0104] The specific parameters of Examples 2-10 and Comparative Examples 1-5 are shown in Tables 1 and 2. Other parameters are the same as those of Example 1. In Table 1, in the column of carbonization temperature, the carbonization process of Examples 3-9 and Comparative Examples 2, 4 and 5 is solid phase mixing and coating.

[0105] Comparative Example 4 LFP was directly coated with O3 phase lithium cobalt oxide without step (2) to prepare P2 phase sodium cobalt oxide or ion exchange. The process of coating LFP with O3 phase lithium cobalt oxide is as follows: LFP in Example 1 and O3 phase lithium cobalt oxide are mixed and heated to the coating sintering temperature (i.e. the first sintering temperature) of 650°C at 5°C / min. The first sintering is carried out for 6 hours to obtain LFP coated with O3 phase lithium cobalt oxide. The carbonization parameters are the same as in Example 3 (i.e., solid phase mixing and coating with ascorbic acid in a certain proportion).

[0106] Comparative Example 5 Ni 0.8 Co 0.1 Mn 0.1 O2OH precursor was mixed with LiOH·H2O at a Li / (Ni+Co+Mn) molar ratio of 1.05, sintered at 850℃ for 16 h, and then crushed after cooling to obtain LiNi. 0.8 Co 0.1 Mn 0.1 O2 (NCM811). The LFP and LiNi from Example 1 were used. 0.8 Co 0.1 Mn 0.1 O2 was mixed, and the temperature was increased at 5℃ / min to the coating sintering temperature (i.e., the first sintering temperature) of 650℃. The first sintering was carried out for 6 hours to obtain LiNi. 0.8 Co 0.1 Mn 0.1 O2-coated LFP; carbonization parameters are the same as in Example 3.

[0107] Performance testing: (1) Ratio performance: CR2430 button cell battery (2C, 5C, 10C rate testing), voltage range 2.0V~3.75V, tested at room temperature: 1. Let stand for 3 minutes; 2. Charge at a constant current of 0.2C to 3.75V, then maintain constant voltage until the current drops to 0.05C; 3. Let stand for 3 minutes; 4. Discharge at a constant current of 0.2C to 2.0V to complete the benchmark test; 5. Switch between 2C, 5C, and 10C in sequence, repeating the above charge and discharge process, with each rate cycled 5 times.

[0108] Full battery (0.33C, 1C, 2C, 5C rate testing), voltage range 2.5~3.65V, tested at a low temperature of -20℃: 1. Let stand for 3 minutes; 2. Charge at the corresponding rate with constant current to 3.65 V, then maintain constant voltage until the current drops to 0.05C; 3. Let stand for 3 minutes; 4. Discharge to 2.5V with constant current at the corresponding rate; 5. Test in the order of 0.2C→0.33C→1C→2C→5C, with 5 cycles for each rate.

[0109] (2) Charge-discharge plateau potential difference: The charge-discharge plateau voltage of the positive electrode material was recorded using a coin cell, and the difference between them was calculated. During the constant current charge-discharge stage at a rate of 0.2C, the voltage-capacity curve was recorded, and the voltage corresponding to 50% of the discharge capacity was taken as the plateau voltage, which was denoted as the charging plateau voltage (V1) and the discharging plateau voltage (V2) respectively. The difference ΔV = V1-V2 was calculated, which is the charge-discharge plateau potential difference. The charge-discharge plateau potential difference directly reflects the degree of electrochemical polarization of the electrode. The smaller the difference, the smaller the polarization of the positive electrode material, the smaller the charge transport resistance, and the better the kinetic performance.

[0110] (3) First-time efficiency - full battery: 0.1C constant current charging to 3.65V, constant voltage to 0.05C, stand for 3 minutes, 0.1C constant current discharging to 2.5V. First-time efficiency = (first discharge capacity / first charge capacity) × 100%.

[0111] (4) Cycle life - full battery: 1C constant current charging to 3.65V, constant voltage to 0.05C, stand for 3 minutes and then 1C constant current discharge to 2.5V, repeat 600 cycles, record the capacity retention rate of 1C / 1C after 600 cycles, capacity retention rate = (discharge capacity of the 600th cycle / discharge capacity of the 1st cycle) × 100%.

[0112] Table 1

[0113] Table 2

[0114] Table 3

[0115] Table 4

[0116] Scanning electron microscopy (SEM) tests were performed on the cathode materials of Example 1 and Comparative Examples 1-2. Figure 2 This is a SEM image of the cathode material in Example 1. Figure 3 and Figure 4 SEM images of the cathode materials of Comparative Example 1 and Comparative Example 2, respectively.

[0117] Conclusion: The cathode material of this application adopts a dual coating strategy of O2 phase lithium cobalt oxide and carbon layer, which synergistically optimizes the electrochemical performance and interface stability of phosphate material, significantly reduces polarization of cathode material under fast charging conditions, greatly improves rate discharge performance, and effectively suppresses capacity decay and increased polarization at low temperature.

[0118] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0119] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0120] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A positive electrode material, characterized in that, The cathode material includes positive electrode particles, which include a phosphate core, an O2 phase lithium cobalt oxide functional layer, and a carbon functional layer. The O2 phase lithium cobalt oxide functional layer covers the surface of the phosphate core, and the carbon functional layer covers the surface of the O2 phase lithium cobalt oxide functional layer away from the phosphate core.

2. The cathode material according to claim 1, characterized in that, The phosphate core comprises the compound shown in Formula 1: LiFe a M b PO4 Formula 1 Wherein, 1≥a>0.5, b≥0, and a+b=1, and M includes at least one of Ni, Co, Mn, Ti, Al, F, B, Si, V, W, Y, Mg, Na, Nb, N, and Ca.

3. The cathode material according to claim 1, characterized in that, The O2 phase lithium cobalt oxide functional layer includes the compound shown in Formula 2: Li x Co m X n O2 Formula 2 Wherein, 0.5≤x<1, 1≥m>0.5, n≥0, and m+n=1, and X includes at least one of Ni, Mn, Ti, Al, F, B, Si, V, W, Y, Mg, Na, Nb, N, and Ca.

4. The cathode material according to claim 1, characterized in that, At least one of the following conditions must be met: The carbon functional layer accounts for 0.1 wt% to 10 wt% of the total mass of the cathode material; The O2 phase lithium cobalt oxide functional layer accounts for 0.1wt% to 5wt% of the total mass of the cathode material.

5. The positive electrode material according to claim 1, characterized in that, The O2 phase lithium cobalt oxide functional layer includes a porous structure, and at least a portion of the carbon functional layer fills the porous structure of the O2 phase lithium cobalt oxide functional layer.

6. A method for preparing the cathode material according to any one of claims 1 to 5, characterized in that, include: An O2 phase lithium cobalt oxide functional layer is formed on the phosphate surface to obtain the first product; A carbon functional layer is formed on the surface of the first product to obtain a cathode material.

7. The method according to claim 6, characterized in that, The formation of the O2 phase lithium cobalt oxide functional layer on the phosphate surface yields a first product, comprising: Provide P2 phase sodium cobaltate; The P2 phase sodium cobaltate and the phosphate are mixed and coated, and then subjected to a first sintering, so that the P2 phase sodium cobaltate coats the surface of the phosphate, to obtain an intermediate product; The intermediate product and lithium source are mixed and subjected to an ion exchange reaction to form an O2 phase lithium cobalt oxide functional layer on the phosphate surface, thus obtaining the first product. The first product and a carbon source are mixed and carbonized to form a carbon functional layer on the surface of the first product, thereby obtaining the cathode material.

8. The method according to claim 7, characterized in that, At least one of the following conditions must be met: The mass ratio of the P2 phase sodium cobaltate to the phosphate is 0.1~5; The molar ratio of sodium in the P2 phase sodium cobaltate to lithium in the lithium source is 1:2~20; The mass of the carbon source is 8wt% to 20wt% of the mass of the phosphate.

9. The method according to claim 7 or 8, characterized in that, At least one of the following conditions must be met: The lithium source includes at least one of LiCl, LiNO3, and LiOH; The carbon source includes at least one of ascorbic acid, α-naphthol, o-naphthol, D-sorbitol, citric acid, oxalic acid, and chitosan.

10. The method according to claim 7, characterized in that, At least one of the following conditions must be met: The first sintering temperature is 200℃~900℃; The first sintering time is 3h~22h; The heating rate of the first sintering is 0.5℃ / min to 8℃ / min; The temperature of the ion exchange reaction is 100℃~400℃; The ion exchange reaction takes 0.5 h to 7 h. The carbonization treatment temperature is 180℃-400℃; The carbonization process takes 3-8 hours. The atmosphere for the carbonization process includes an inert gas.

11. A positive electrode plate, characterized in that, The cathode material includes any one of claims 1 to 5 or the cathode material prepared by any one of claims 6 to 10.

12. A battery, characterized in that, The cathode material includes any one of claims 1 to 5, the cathode material prepared by any one of claims 6 to 10, or the cathode sheet as described in claim 11.

13. An electrical appliance, characterized in that, The cathode material includes any one of claims 1 to 5, the cathode material prepared by any one of claims 6 to 10, the cathode sheet of claim 10, or the battery of claim 12.